2009
DOI: 10.1016/s0034-7094(09)70081-9
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of Postoperative Nausea and Vomiting in Morbidly Obese Patients Undergoing Laparoscopic Gastroplasties. A Comparative Study among Three Methods

Abstract: The incidence of postoperative nausea and vomiting in videolaparoscopic gastroplasties was more effectively reduced with the association of ondansetron and dexamethasone than with each drug separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 9 publications
1
6
2
1
Order By: Relevance
“…The current study compared the frequency of postoperative nausea in morbidly obese and normal weight to mildly obese patients in 138 cases and observed significant differences concerning the study population. The frequency of PONV in the OG we observed in the current study was comparable to other investigations [11, 12]. In addition, the occurrence of PONV was more frequent in female subjects and, thus, corresponds to the results reported by Apfel et al [1, 13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study compared the frequency of postoperative nausea in morbidly obese and normal weight to mildly obese patients in 138 cases and observed significant differences concerning the study population. The frequency of PONV in the OG we observed in the current study was comparable to other investigations [11, 12]. In addition, the occurrence of PONV was more frequent in female subjects and, thus, corresponds to the results reported by Apfel et al [1, 13].…”
Section: Discussionsupporting
confidence: 92%
“…However, in the field of bariatric surgery, up to now, there is only a small number of studies focusing on PONV rates and their cause. Mendes et al and Moussaa et al reported on PONV-incidences up to 79% in bariatric patients [11, 12]. In a study published by Bataille et al , who examined PONV rates when using total intravenous anaesthesia with BIS monitoring, PONV frequency was up to 54% [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nausea and vomiting were n Number of patients present in 33 (41.3%) and 28 (35%) patients, consecutively. Although nausea and vomiting had been reported as ones of the presenting symptoms in leak patients after LSG [13], they are also common in up to 79% of patients in the early postoperative period [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Тошнота и рвота в послеоперационном периоде при бариатрических вмешательствах встречаются у 70-80% пациентов, если пациенты не получают антиэметическую профилактику [32,33] Применение любого из этих препаратов интраоперационно перед окончанием операции достоверно снижает частоту эпизодов тошноты и рвоты в послеоперационном периоде, однако сочетанное применение этих препаратов позволяет добиться еще более значительного снижения частоты и интенсивности этих симптомов (с 79% до 19%) [36] и уменьшить потребность в обезболивании в послеоперационном периоде [37]. В систематическом обзоре не было выявлено побочных эффектов в виде увеличения частоты послеоперационных инфекций или замедленного заживления ран после однократного болюсного введения дексаметазона [38].…”
Section: можно рекомендовать антибиотикопрофилактику цефалоспоринами unclassified